2008
DOI: 10.1094/mpmi-21-7-0958
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Drought Tolerance and Grain Yield in Common Bean by Overexpressing Trehalose-6-Phosphate Synthase in Rhizobia

Abstract: Improving stress tolerance and yield in crops are major goals for agriculture. Here, we show a new strategy to increase drought tolerance and yield in legumes by overexpressing trehalose-6-phosphate synthase in the symbiotic bacterium Rhizobium etli. Phaseolus vulgaris (common beans) plants inoculated with R. etli overexpressing trehalose-6-phosphate synthase gene had more nodules with increased nitrogenase activity and higher biomass compared with plants inoculated with wild-type R. etli. In contrast, plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
139
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(159 citation statements)
references
References 44 publications
9
139
3
3
Order By: Relevance
“…Trehalose is also implicated as a signal molecule during formation of rhizobial and mycorrhizal symbioses (Fig. 1) and in interactions with other beneficial microbes (Suárez et al, 2008;Rodríguez-Salazar et al, 2009;Fernandez et al, 2010Fernandez et al, , 2012. As these topics have been covered in a recent review , and no specific function for Tre6P in plant-microbe interactions (beyond the synthesis of trehalose) has so far been clearly identified, we shall focus here on the role of Tre6P in plant responses to abiotic stress.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%
“…Trehalose is also implicated as a signal molecule during formation of rhizobial and mycorrhizal symbioses (Fig. 1) and in interactions with other beneficial microbes (Suárez et al, 2008;Rodríguez-Salazar et al, 2009;Fernandez et al, 2010Fernandez et al, , 2012. As these topics have been covered in a recent review , and no specific function for Tre6P in plant-microbe interactions (beyond the synthesis of trehalose) has so far been clearly identified, we shall focus here on the role of Tre6P in plant responses to abiotic stress.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%
“…Rhizobacteria engineered to overexpress trehalose biosynthetic genes improved the drought tolerance of the plants inoculated with the modified rhizobia strains. Common bean plants (Phaseolus vulgaris) inoculated with Rhizobium etli overexpressing trehalose-6-phosphate synthase recovered completely when exposed to drought stress as opposed to plants inoculated with the wild type strain, which wilted and died (Suarez et al, 2008). Maize plants inoculated with Azospirillum braziliense overexpressing trehalose biosynthetic genes had an 85% of survival following drought stress compared to 55% survival rate in the case of the plants inoculated with the untransformed strain (Rodriguez-Salazar et al, 2009).…”
Section: Bacteriamentioning
confidence: 99%
“…Trehalose accumulation has also been correlated with improved stress tolerance in free-living cells of R. etli (Suarez et al, 2008). Suarez et al (2008) found that a strain of R. etli that overexpresses OstA (Ox) grew to significantly higher numbers under hyperosmotic conditions than the wild-type (WT) and an ostA deficient mutant (ostA -).…”
Section: Role Of Trehalose In Desiccation Tolerancementioning
confidence: 99%
“…Suarez et al (2008) found that a strain of R. etli that overexpresses OstA (Ox) grew to significantly higher numbers under hyperosmotic conditions than the wild-type (WT) and an ostA deficient mutant (ostA -). Exponentially grown cells of the Ox strain were also reported to survive significantly better after exposure to heat shock and when freeze-thawed prior to plating.…”
Section: Role Of Trehalose In Desiccation Tolerancementioning
confidence: 99%
See 1 more Smart Citation